Juventude em conflito com a lei: expressões objetivas e subjetivas das opressões em capitais do Nordeste brasileiro - Samira Safadi Bastos (Desidades, 2020)
This article synthesized the doctoral research made on 15-24 year olds, Northeastern brazilians, black, in open social-educational measure, aiming to study the effects of generational transmission/oppression of poverty, racialization and the gender, in view of the objective and subjective material conditions of those young men facing the resurgence of Brazilian neoliberalism. Semi-structured interviews were conducted, whose analysis — vertical and horizontal — were based on historical-dialectical materialism. In the composition of the theoretical basis and approximation with similar researches, it was noticed the capillarization of the punitivist system, that massively incarcerates young black people and commits black genocide, besides the increasing criminalization of social movements that react to this. Impacts, in the sense of recognition, valorization, belonging, affiliation, virilism, articulated to the social unprotection of families and maintenance of familism by social policies, female single parenting and the criminalization of poverty through the current drug policy resulted from this analysis, entailing in overlapping oppressions.